2017
DOI: 10.1177/0193723517705545
|View full text |Cite
|
Sign up to set email alerts
|

Marketing and Advertising Online Sports Betting: A Problem Gambling Perspective

Abstract: In this article, online sports betting is explored with the objective of critically examining the potential impact on problem gambling of the emerging product features and advertising techniques used to market it. First, the extent of the issue is assessed by reviewing the sports betting prevalence rates and its association with gambling disorders, acknowledging the methodological difficulties of an unambiguous identification of what exactly constitutes sportsrelated gambling today. Second, the main changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 43 publications
7
75
0
1
Order By: Relevance
“…The interaction in this study between a number of sports-related variables such as watching live sports, in-play betting, and fantasy and gambling involvement suggests that sports fandom might be playing a role in the cross-fertilization of different activities that are not inherently linked to sports. This adds to the idea that those sports fans with stronger and deeper ties to sport (e.g., team identification) might be more vulnerable to the promotions and marketing strategies of fantasy and gambling products addressed at them (Deans et al 2016b;Lopez-Gonzalez et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction in this study between a number of sports-related variables such as watching live sports, in-play betting, and fantasy and gambling involvement suggests that sports fandom might be playing a role in the cross-fertilization of different activities that are not inherently linked to sports. This adds to the idea that those sports fans with stronger and deeper ties to sport (e.g., team identification) might be more vulnerable to the promotions and marketing strategies of fantasy and gambling products addressed at them (Deans et al 2016b;Lopez-Gonzalez et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Research focusing on newer forms of gambling, such as online sports betting, shows that children have a significant recall of sports betting brands when they are aligned with culturally valued activities such as sport, as well as specific recall of advertising creatives, plot lines and promotions 11,16 . Researchers have also demonstrated that the alignment of marketing for these products with sport may be having an influence on normalising children's perceptions that gambling is a ‘normal’ or ‘common’ part of sport, 10,26,27 and that children's recall of inducement and incentive promotions used by sports betting companies, such as ‘free’ bets and ‘cash back’ offers, may reduce children's perceptions of the risks associated with gambling 28 …”
Section: Advertising Strategies and The Impact On Children's Attitudementioning
confidence: 99%
“…Although historically, sports betting has not been recognised as a particularly risky form of gambling (Lopez-Gonzalez et al 2017), many researchers have argued that the development and expansion of the structural features of online sports betting are leading to an increased risk for gambling-related harm (Hing et al 2016a, b;Hing et al 2014b). More specifically, instant accessibility and the transformation of online sports betting towards a more continuous gambling format have been identified as factors that are likely to increase disordered gambling behaviour (Hing et al 2014b;Killick and Griffiths 2018;Lopez-Gonzalez et al 2017.…”
Section: Introductionmentioning
confidence: 99%